Religious architecture in the era of the ancient Egyptian state (Journal of the College of Basic Education, 2023)
The Egyptian architecture used adobe in its early beginning , and then used stone extensively at the time of the founder of the third dynasty, King (Djoser), and at the hands of the professional engineer (Imhotep). The architecture began with simple forms such as the royal tombs, which consisted of square-shaped terraces and simple installation, and then developed into what is known as the pyramids, by adding multiple terraces, as is the case in the step pyramid of King Djoser. As for the temples, they varied, some of them were for the sun god or the other deity, and some of them were known as the funerary temples attached to the pyramids, and some of them were known as the valley temples. The research includes three axes, the first deals with the history of Egypt in the era of the Old Kingdom, and in the second axis it deals with the impact of religious belief on the genera form of architecture.